Voting in Local Political Elections by Urban Chinese Middle Class: Does Housing Matter? (Asian Journal of Social Science Studies, 2016)
This paper examines the impact of types of housing on the tendency to engage in neighborhood-level political participation among urban residents in China, using 2005 China General Social Survey. Four types of housing were discussed: commercial housing; previously state-owned (work unit) housing; old neighborhood; and other types of housing (i.e. migration housing). Two indicators of local political participation were presented in the form of Local People’s Congress elections and Residents’ Committee elections. Using multivariate logistic regression analysis, the authors found that types of housing had strong implications for voting in local elections among Chinese urban residents. First, the likelihood of voting in two local elections was lowest among residents living in commercial housing, and the highest in old neighborhoods. Second, participation in community-led venues (i.e. cultural events) enhanced the voting rate among residents living in commercial housing. Results highlight the importance of the sweeping housing reform in urban neighborhoods to local political participation in contemporary China, and the changing relationship between state and society. Although rapid economic reform has diversified and alienated the neighborhood, community-led civic activities can reunify the residents and enhance their local political participation. This effect was more significant among the young, college-educated, high-income middle class.